Quantitative Simulation of Damage Roots on Inoculated Alfalfa by Arbuscular Mycorrhiza Fungi - Ying Liu (International Journal Bioautomation, 2017)
Underground mining would cause ground subsidence damage and large amounts of cracks, which would result a loss of surface moisture and nutrient and intensifying drought. There are a few reports about damage to plant roots caused by coal mining. The irregular distribution of plant roots in soil and the different forces generated in process of surface subsidence are difficult to study comprehensively. The technologies to repair damaged plant roots have not been completely perfected yet. Based on quantitative simulation of alfalfa root cut-repair experiment, this paper discusses the influences of inoculated Arbuscular Mycorrhiza Fungi on alfalfa root and the mitigation effects of an inoculation on the growth of alfalfa. Root injured alfalfa were investigated by soil pot experiments. The result indicated that at the same cut degree, the growth situation of inoculated alfalfa is better than the contrast. Compared with the Olsen-P content, at cut level of 0 and 1/3, the sand of inoculated alfalfa has less Olsen-P than contrast, at cut degree of 1/2 and 2/3, the sand of inoculated alfalfa has more Olsen-P than contrast, at degree of 3/4, the sand of inoculated alfalfa has less Olsen-P than contrast, the change trend of Olsen-P content is concerned with the relative strength size of absorb Olsen-P by alfalfa root and dissolve Olsen-P by root exudates and hyphae interstate.